Knowledge and Myths About Child Sexual Abuse in Mexican Women - Rueda, Pilar (Journal of interpersonal violence, 2022)
Child sexual abuse (CSA) is a terrible type of maltreatment that occurs in all countries and social statuses, but due to the shame and taboo that it creates, it is still riddled with myths and false beliefs that make it difficult for the population and the authorities to adequately determine its prevalence. The objective of this work was to explore what Mexican women know about CSA. The participants were Mexican women (N?=?499) who filled out a questionnaire comprising ten items referring to truths and myths about CSA, indicating their degree of agreement with them on a Likert scale. The results showed that although Mexican women have quite adequate knowledge about CSA, they still hold wrong beliefs about the child?s feelings toward the abuser or the child victim becoming an adult abuser. Likewise, differences were found in the myths and truths about CSA held by women under 40 and over 40?years of age.